Supplementation with organic or inorganic selenium in heat-distressed quail - Şahin, Nurhan; Onderci, Muhittin; Şahin, Kazım; Küçük, Ömer (Springernature, 2008)
The present study was carried out to determine the effects of different sources of selenium (Se; sodium selenite [Na2SeO3] or selenomethionine [Se-Met]) supplementation on egg production, egg quality, levels of malondialdehyde (MDA), and Se in serum and egg yolk in heat-stressed Japanese quail (Coturnix coturnix japonica). The birds (n = 360; 55 days old) were randomly assigned to 12 treatment groups consisting of six replicates of five birds each in a 2 x 2 x 3 factorial arrangement of treatments (temperatures, selenium sources, selenium levels). Birds were kept in wire cages in a temperature-controlled room at either 22 (thermoneutral) or 34 degrees C (heat stress) for 8 h/day (09:00-17:00; till the end of study) and fed a basal (control) diet or the basal diet supplemented with either 0.15 or 0.30 mg of Na2SeO3 or selenomethionine/kg of diet. Heat exposure decreased live weight, feed intake, feed efficiency, egg production, and egg quality when basal diet was fed (P < 0.0001). A linear increase in feed intake (P = 0.001) and body weight (P = 0.001), egg production (P = 0.001), and improvement in feed efficiency (P = 0.001) and egg quality (P = 0.001) were found in Se-supplemented quail reared under heat stress conditions. Serum, egg white, and egg yolk Se (P <= 0.001) concentrations increased linearly, whereas serum, liver, and egg yolk MDA concentrations decreased linearly (P = 0.001) as dietary Na2SeO3 or Se-Met supplementation increased. An interaction between dietary Se sources, temperature, and levels of supplementation (P <= 0.05) for these parameters was detected. Supplementation with Se improved egg production, egg quality, and antioxidant status of birds, and the effects of Se-Met were relatively greater than Na2SeO3 in heat-stressed quail. Results of the present study suggest that supplementation with Se-Met can be considered to be more protective than Na2SeO3 by reducing the negative effects of oxidative stress induced by heat stress in quail.
Keywords: selenium; heat; stress; quail